Survey on the Progression of Myopia in Children and Adolescents in Chongqing During COVID-19 Pandemic - Wang, Wujiao; Zhu, Lu; Zheng, Shijie; Ji, Yan; Xiang, Yongguo; Lv, Bingjing; Xiong, Liang; Li, Zhuoyu; Yi, Shenglan; Huang, Hongyun; Zhang, Li; Liu, Fangli; et al. (Frontiers in Public Health, 2021)
Background: The Covid-19 pandemic restricts children and adolescents from doing normal daily activities such as playing outdoors and going to school. The incidence and prevalence of myopia have increased during the COVID-19 pandemic. The aim of this study was to investigate and evaluate the impact of the home confinement during the COVID-19 pandemic on the progression of myopia among children and adolescents in Chongqing, China. Methods: The survey was conducted by using stratified samplings. Samples were randomly selected from the 2019 National Student Physique and Health Survey database, and their visual function and refractive data were compared with those in 2020. Vision-related behavior questionnaire including digital screen exposure was applied to investigate the correlation between eye parameter and eye health-related behavior. Results: A total of 1,733 and 1,728 students were enrolled in 2020 and 2019, respectively. The percentage of myopia students was 55.02% in 2020, which was higher than that in 2019 (44.62%). The mean uncorrected visual acuity (UCVA, LogMAR, 0.35 ± 0.42) in 2020 was higher than that in 2019 (0.27 ± 0.36, P < 0.001). The mean spherical equivalent (SE) refraction (−1.94 ± 2.13 D) in 2020 was lower than that in 2019 (−1.64 ± 5.49 D, P < 0.001). For students who used digital devices for online courses, the mean SE in the television group (−1.10 ± 1.49 D) was better than that in the computer group (−2.03 ± 2.37 D, P = 0.0017) and in the cell phone group (−2.02 ± 2.09 D, P = 0.0028). The average duration of online classes (r = −0.27, P < 0.0001), the number of online classes per day (r = −0.33, P < 0.0001), as well as digital screen exposure time (r = −0.20, P < 0.0001) were negatively correlated with SE, and the average time of outdoor activity (r = 0.20, P < 0.0001) was positively correlated with SE. Conclusions: Increased digital screen exposure contributes to myopic progression in children and adolescents of Chongqing during the COVID-19 pandemic. Suitable digital devices should be provided for online classes and outdoor activity should be advocated to prevent myopic pandemic.